EAST OR WEST, RODINA IS BEST: SHAPING A SOCIALIST 'HEIMAT' IN GERMAN AND SOVIET FILM OF THE OCCUPATION PERIOD. (October 2016) - Kostetskaya, Anastasia
ABSTRACT: This essay examines how films of the occupation period encode the gradual consolidation of a post‐war national identity for East Germans in the emerging GDR. For this purpose, this article offers a comparative analysis of the two films Irgendwo in Berlin (1946) by Gerhardt Lamprecht and U nikh est' rodina (1949) by Aleksandr Fainzimmer, translated into German as Sie haben eine Heimat . I focus on how the films employ images of children in order to foreground and illuminate the culturally specific but overlapping concepts of homeland – 'Heimat' and rodina – as essential for the ideas of nation and belonging. Both films provide ideological commentary on the post‐war occupation of Germany through the theme of the family fragmented by the war and the need for familial restoration. Hence a child‐parent paradigm becomes central to the exposition of the opposing perspectives: those of the infantilised occupied and the paternalistic occupier. My discussion uncovers cross‐cultural, historical continuity between the films. It demonstrates that the Soviet film provides 'solutions' to the problems of German post‐war identity posed in Irgendwo in Berlin, while the concept of 'Heimat' offers a viable framework for the appropriation of Soviet‐style socialism by the GDR. Dieser Aufsatz untersucht, wie Filme der Besatzungszeit die allmähliche Festigung der staatlichen Nachkriegsidentität der Ostdeutschen in der Sowjetischen Besatzungszone kodieren. Dazu wird eine vergleichende Analyse von zwei Filmen, Irgendwo in Berlin (1946) von Gerhardt Lamprecht, und U nikh est' rodina (1949) von Aleksandr Fainzimmer, übersetzt ins Deutsche als Sie haben eine Heimat, vorgelegt. Ich konzentriere mich darauf, wie die Filme Darstellungen von Kindern nutzen, um die kulturspezifischen aber überlappenden Konzepte des Geburtslandes – Heimat und rodina – als wesentlich für die Vorstellung von Nationalität und Zugehörigkeit zu beleuchten. Beide Filme liefern mit dem Motiv der im Krieg zerrütteten Familie und der Notwendigkeit der Familienerneuerung einen ideologischen Kommentar zur Besetzung Deutschlands. Daher wird ein Eltern‐Kind‐Paradigma zum zentralen Element bei der Darstellung gegensätzlicher Perspektiven: der des infantilisierten Besetzten und der des paternalistischen Besetzers. Meine Erörterung zeigt eine interkulturelle historische Kontinuität zwischen den beiden Filmen auf. Sie veranschaulicht, dass der sowjetische Film 'Lösungen' für die in Irgendwo in Berlin aufgeworfenen Probleme der deutschen Nachkriegsidentität bietet, während das Heimat‐Konzept einen praktikablen Rahmen für die Aneignung eines Sozialismus sowjetischen Stils durch die DDR bietet.